As origens do movimento ecumênico na Amazônia Paraense - Silva, Antonio Carlos Teles da (2005)
The purpose of this study is to describe the emergence of the ecumenical movement in the Amazon Region within the state of Para. It identifies its origin among the mobilizations for the Araguaia prisoners liberation in the early 80 s. Such identification presupposes an analysis of the movement and its relation with the political situation in Brazil at the end of the military government, as well as an analysis of its relationship with social movements against rural violence in Amazonia, specifically in the Araguaia region. The author demonstrates that the identity and the development of the ecumenical movement is marked by its commitment with the reality in the Amazone region. At the same time, this ecumenical movement recognizes itself as a part of the ecumenical tradition and of the ideal of unity as represented by the historical and worldwide ecumenical movement. The author bases his theoretical analysis on the concept of base ecumenism as a religious phenomenon of great importance in Latin America, in close connection with Liberation Theology in its preferential option for the poor and the landless.